Pathways out of ultra-poverty: A mixed methods assessment of layered interventions in coastal Bangladesh - Diwakar, Vidya; Kamninga, Tony; Mehzabin, Tasfia; Tumusiime, Emmanuel; Kamal, Rohini; Pabony, Nuha Anoor (Chronic Poverty Advisory Network, 2024)
Studies suggest impoverishment in Bangladesh has been driven by climate-change-related shocks, ill-health and healthcare expenses, poor access to agricultural markets and services, and more recently, the COVID-19 pandemic. Multi-sectoral programmes have the potential to address these challenges. This research explores the potential of multi-sectoral integration and layering of the Ultra Poor Graduation (UPG) programming combined with inclusive Market Systems Development (iMSD); climate-related Disaster Risk Reduction (DRR); and Water, Sanitation and Hygiene (WASH) interventions to enhance individual and community level resilience capacities and prevent re-entry of participants of the UPG program into poverty. We examined this potential in southwest Bangladesh based on the Nobo Jatra Project (NJP), a Resilience and Food Security Activity (2015- 2022) funded by USAID and implemented by a consortium of NGOs led by World Vision. We used a mixed methods research approach to examine and compare wellbeing and resilience indicators among a sample of respondents of NJP exposed to different combinations of the interventions. The study set out to test three hypotheses which have been used to organize the key findings and programming recommendations. The results show that participation in the UPG programme with iMSD is associated with the development of absorptive and adaptive capacities that can tackle chronic poverty. Secondly, strengthening resilience capacities to anticipate and absorb disaster and health shocks may prevent households from falling back or deeper into ultra-poverty. Moreover, transformative actions such as women empowerment, access to markets, participation in savings groups, and social networks improve women’s ability to sustain escapes from poverty.